Nilai-Nilai Pendidikan Karakter Sosial perspektif Al-Qur’an dan Urgensinya dalam Masyarakat Multikultural - Arinda Rosalina (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2025)
The values ​​of social character education in the Qur'an are the principles, norms, and goodness towards social character in social interactions that are understood through the explanation of the verses of the Qur'an. This article is motivated by the existence of deviations in the socio-cultural environment of a multicultural society which of course causes discomfort. This article focuses on the analysis of the values ​​of social character education from the perspective of the Qur'an and its urgency in a multicultural society. This article uses a library research approach with primary data sources in the form of interpretations or opinions of scholars regarding verses on the values ​​of social character education. In addition, secondary data in the form of books, journals and other literature that specifically discuss the values ​​of social character education from the perspective of the Qur'an and its urgency in a multicultural society. Data analysis in this study uses content analysis steps that adopt Krippendorff's idea consisting of sample unitization, categorization, data reduction, conclusions and justification of research data in the form of verses on the values ​​of social character education. This article shows that 13 values ​​of social character education come from the verses of the Qur'an. These values ​​are important in promoting peace and harmony within the identity of a multicultural society.